The Impact of Faith-Based Pastoral Care in Decreasingly Religious Contexts: The Australian Chaplaincy Advantage in Critical Environments - Layson, Mark D. (Journal of religion and health, 2023)
This article considers the contribution of faith-based chaplains who provide holistic pastoral and spiritual care within critical environments such as the military, first responders, and hospitals. The contribution of faith-based chaplains can sometimes be taken for granted or not properly understood, particularly in some Western countries which are currently experiencing a decline in religiosity. Following on from a previous paper regarding chaplaincy utilization (Layson et al. 2022), this article presents an alternative argument to the secularist-humanist perspective by noting five ways by which the faith based chaplaincy model provides best practice service and builds a capability advantage for organizations that engage faith-based chaplaincy services. The first section discusses faith-based chaplaincy and organizational holistic care; the second section considers the role of faith-based chaplains—much of which is largely unknown and poorly appreciated; the third section considers the unique capability of faith-based chaplains to provide spiritual and religious care to those of faith and for those of none; the fourth section explores how faith-based chaplains can leverage the positive impact of religious organizations to provide additional low-cost resources for other organizations and their staff; and lastly, the operational advantage of faith-based chaplains on the world stage is considered, particularly in light of culturally and linguistically diverse populations to whom religiosity is increasingly important.